Bladder and rectum dose estimations on digitized radiographs for vaginal brachytherapy after hysterectomy. (8th November 2014) - Zhang, Winson; Bhatia, Sudershan K.; Sun, Wenqing; Modrick, Joseph M.; Kim, Yusung
Abstract : The purpose of this study was to evaluate the feasibility of assessing bladder and rectal point doses, using orthogonal radiographs without treatment planning, for vaginal cylinder applicator (VC), high‐dose‐rate (HDR) vaginal cuff brachytherapy (BT) after hysterectomy. Thirty‐three VC HDR BT treatment plans from 31 postoperative endometrial cancer patients were retrospectively analyzed. Single‐channel VC with four differing diameters — 2.0 cm, 2.3 cm, 2.6 cm, and 3.0 cm — were analyzed. Dose‐distance modeling was performed to estimate bladder and rectal point doses by measuring distances on each orthogonal radiograph without treatment planning. The estimated doses were then compared with doses calculated on treatment planning system (TPS). Their percent (%) dose differences were recorded. Analysis was performed for each VC size, ICRU bladder and rectal points, and the closest rectal point. The estimated doses obtained from dose‐distance modeling displayed on average less than 2.5% difference when compared with TPS doses at ICRU bladder and rectal points for each VC size. Dose percent differences between estimated values and TPS values were on average 1.9% and 2.5% for ICRU bladder and rectal point, respectively, regardless of VC sizes. Dose‐distance modeling for closest rectal point presented on average 5.4% dose difference when compared with TPS values of all VC sizes. It was feasible to estimate rectal and bladder point doses by measuring distances on orthogonal radiographs without treatment planning. Percent dose differences were 2.5% less for both ICRU bladder and rectal points, regardless of VC sizes. The use of closest rectal point is not recommended for estimating rectal dose. PACS number: 87.53.‐j, 87.53.Jw, 87.55.‐x, 87.55.D‐, 87.55dk